2020
DOI: 10.1109/tpwrs.2019.2948132
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Tap Setting of Voltage Regulation Transformers Using Batch Reinforcement Learning

Abstract: In this paper, we address the problem of setting the tap positions of load tap changers (LTCs) for voltage regulation in radial power distribution systems under uncertain load dynamics. The objective is to find a policy to determine the tap positions that only uses measurements of voltage magnitudes and topology information so as to minimize the voltage deviation across the system. We formulate this problem as a Markov decision process (MDP), and propose a batch reinforcement learning (RL) algorithm to solve i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 28 publications
0
61
0
Order By: Relevance
“…A distributed Q-learning is implemented to coordinate generators, OLTCs, and capacitors in [14] for optimal reactive power dispatch. Batch reinforcement learning is applied to achieve cooperation of OLTCs for voltage regulation [15]. Coordination between OLTCs and capacitors are studied with policy gradient method for voltage violation mitigation and operation cost reduction [16].…”
Section: Introductionmentioning
confidence: 99%
“…A distributed Q-learning is implemented to coordinate generators, OLTCs, and capacitors in [14] for optimal reactive power dispatch. Batch reinforcement learning is applied to achieve cooperation of OLTCs for voltage regulation [15]. Coordination between OLTCs and capacitors are studied with policy gradient method for voltage violation mitigation and operation cost reduction [16].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure of leveraging this relaxed set (instead of the nonconvex one) is known as SOCP relaxation [32]. Interestingly, it has been shown that under certain conditions, SOCP relaxation is exact in the sense that the set of inequalties (6) holds with equalities at the optimum [33]. Given the capacitor configurationŷ y y(τ ) found at the end of the last interval τ − 1, under the aforementioned relaxed grid model, the voltage regulation on the fast timescale based on the exact AC model can be described as follows…”
Section: A Branch Flow Modelmentioning
confidence: 99%
“…However, these approaches can be computationally demanding, and do not guarantee optimal performance. A batch reinforcement learning (RL) scheme based on linear function approximation was lately advocated in [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations